2015
DOI: 10.1002/adma.201502341
|View full text |Cite
|
Sign up to set email alerts
|

Halloysite Clay Nanotubes for Loading and Sustained Release of Functional Compounds

Abstract: Halloysite is an alumosilicate tubular clay with a diameter of 50 nm, an inner lumen of 15 nm and a length of 600-900 nm. It is a natural biocompatible nanomaterial available in thousands of tons at low price, which makes it a good candidate for nanoarchitectural composites. The inner lumen of halloysite may be adjusted by etching to 20-30% of the tube volume and loading with functional agents (antioxidants, anticorrosion agents, flame-retardant agents, drugs, or proteins) allowing for formulations with sustai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

21
462
1
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 840 publications
(517 citation statements)
references
References 124 publications
21
462
1
9
Order By: Relevance
“…Due to its low cost, wide availability, and interesting physico-chemical properties [1], halloysite has attracted considerable attention for applications in many fields [2]. In particular halloysite, being a biocompatible nanomaterial, is perspective as drug carrier and delivery [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Due to its low cost, wide availability, and interesting physico-chemical properties [1], halloysite has attracted considerable attention for applications in many fields [2]. In particular halloysite, being a biocompatible nanomaterial, is perspective as drug carrier and delivery [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…10-30 nm and 40-70 nm, respectively . Halloysite possesses a positive alumina inner lumen and a negative silica outer surface allowing its selective functionalization (Arcudi et al, 2014;Cavallaro, Lazzara, & Milioto, 2012), the formation of a liquid crystalline phase (Luo et al, 2013) and the encapsulation of chemically and biologically active compounds Lvov, Shchukin, Möhwald, & Price, 2008;Lvov, Wang, Zhang, & Fakhrullin, 2016;Lvov, DeVilliers, & Fakhrullin, 2016;Shutava, Fakhrullin, & Lvov, 2014;), such as drugs (Aguzzi, Cerezo, Viseras, & Caramella, 2007;Lun, Ouyang, & Yang, 2014), natural molecules (Massaro, Piana et al, 2015), marine biocides (Wei et al, 2014), cosmetics (Suh et al, 2011), and other functional agents (Abdullayev, Price, Shchukin, & Lvov, 2009). HNT are suitable as catalytic supports (Machado, de Freitas Castro, Wypych, & Nakagaki, 2008;Massaro et al, 2014;, adsorbent nanomaterials for wastewater decontamination (Szczepanik & Słomkiewicz, 2016;Zhang et al, 2016), and nanofiller for sustainable packaging (Liu, Wu, Jiao, Xiong, & Zhou, 2013;Tescione, Buonocore, Stanzione, Oliviero, & Lavorgna, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the chemical makeup of the HNT lumen, it is capable of being doped with a diverse set of substances including antibiotics, chemotherapeutics, growth factors, RNA and DNA, and used as a vehicle for drug transportation and sustained release [20][21][22][23]. Additionally, several recent studies have demonstrated that HNTs are cytocompatible [20,[24][25][26].…”
Section: Introductionmentioning
confidence: 99%